Does a mandibular overdenture improve nutrient intake and markers of nutritional status better than conventional complete denture? A systematic review and meta-analysis. - Yamazaki, T.; Martiniuk, A.; Irie, K.; Sokejima, S.; Lee, Crystal (BM J Group, 2016)
OBJECTIVES: The need for denture treatment in public health will increase as the population ages. However, the impact of dentures on nutrition, particularly overdenture treatment, remains unclear although the physical and psychological effects are known. We investigated whether treatment with a mandibular implant supported overdenture improves nutrient intake and markers of nutritional status better than a conventional complete denture in edentulous patients. DESIGN: Systematic review and meta-analysis. METHODS: Medline, EMBASE and the Cochrane Central Register of Controlled Trials were searched for eligible studies published up to April 2016. We included studies which compared the treatment effect of an overdenture to conventional denture on nutrition, in which primary outcomes included changes in intake of macronutrients and/or micronutrients and/or indicators of nutritional status. Two reviewers independently evaluated eligible studies and assessed the risk of bias. We used a fixed effects model to estimate the weighted mean difference (WMD) and 95% CI for change in body mass index (BMI), albumin and serum vitamin B12 between overdenture and conventional denture 6 months after treatment. RESULTS: Of 108 eligible studies, 8 studies involving 901 participants were included in the narrative appraisal. Four studies reported changes in markers of nutritional status and nutrient intake after treatment with a prosthetic, regardless of type. In a meta-analysis of 322 participants aged 65 years or older from three studies, pooled analysis suggested no significant difference in change in BMI between an overdenture and conventional denture 6 months after treatment (WMD=-0.18 kg/m(2) (95% CI -0.52 to 0.16)), and no significant difference in change in albumin or vitamin B12 between the two treatments. CONCLUSIONS: The modifying effect of overdenture treatment on nutritional status might be limited. Further studies are needed to evaluate the effectiveness and efficacy of denture treatments.